Glycomic analysis of gastric carcinoma cells discloses glycans as modulators of RON receptor tyrosine kinase activation in cancer - Mereiter, S (2016)
Background Terminal a2-3 and a2-6 sialylation of glycans precludes further chain elongation, leading to the biosynthesis of cancer relevant epitopes such as sialyl-Lewis X (SLe X ). SLe X overexpression is associated with tumor aggressive phenotype and patients' poor prognosis. Methods MKN45 gastric carcinoma cells transfected with the sialyltransferase ST3GAL4 were established as a model overexpressing sialylated terminal glycans. We have evaluated at the structural level the glycome and the sialoproteome of this gastric cancer cell line applying liquid chromatography and mass spectrometry. We further validated an identified target expression by proximity ligation assay in gastric tumors. Results Our results showed that ST3GAL4 overexpression leads to several glycosylation alterations, including reduced O-glycan extension and decreased bisected and increased branched N-glycans. A shift from a2-6 towards a2-3 linked sialylated N-glycans was also observed. Sialoproteomic analysis further identified 47 proteins with significantly increased sialylated N-glycans. These included integrins, insulin receptor, carcinoembryonic antigens and RON receptor tyrosine kinase, which are proteins known to be key players in malignancy. Further analysis of RON confirmed its modification with SLe X and the concomitant activation. SLe X and RON co-expression was validated in gastric tumors. Conclusion The overexpression of ST3GAL4 interferes with the overall glycophenotype of cancer cells affecting a multitude of key proteins involved in malignancy. Aberrant glycosylation of the RON receptor was shown as an alternative mechanism of oncogenic activation. General significance This study provides novel targets and points to an integrative tumor glycomic/proteomic-profiling for gastric cancer patients' stratification. This article is part of a Special Issue entitled "Glycans in personalised medicine" Guest Editor: Professor Gordan Lauc.